La fonction rituelle du dispositif Différents et Compétents : ambiguïtés et dons professionnels - Maude Hatano-Chalvidan (Questions Vives)
This article proposes to come back to a particular system of Recognition of Acquired Professional Experience of people with disabilities: Different and Competent, created in 2006. This device has already been the subject of research and interpretations in term of training and support (Laville, Mazereau, 2022). This text thus proposes a new reading of what is at stake within the device which can be read as a form of codified co-activity where the visible testing (passage of the candidate in front of a professional jury) also implies invisibly the testing of the accompanying trainer. This unsaid dimension of the device, in its ritual form produces functional ambiguity (Durkheim, 1991) with which everyone (trainees and trainer) works on their experience and constructs meaning on their experience and by extension on their own social and professional journey. This sense of experience leads us to question the place of a form of “pedagogical gift” at the heart of the trainee and trainer-accompanying relationship.